2019
DOI: 10.3389/fchem.2019.00745
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin-Functionalized Chitosan-Chondroitin Sulfate Hydrogels for Controlled Release of TGF-β3 and in vitro Neocartilage Formation

Abstract: Repair of hyaline cartilage remains a huge challenge in clinic because of the avascular and aneural characteristics and the paucity of endogenous repair cells. Recently, tissue engineering technique, possessing unique capacity of repairing large tissue defects, avoiding donor complications and two-stage invasive surgical procedures, has been developed a promising therapeutic strategy for cartilage injury. In this study, we incorporated low-molecular-weight heparin (LMWH) into carboxymethyl chitosan-oxidized ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…For example, MSCs derived from bone marrow, synovium or adipose tissue reached 80-90% confluence within 7 to 14 days (Zhang et al, 2014;Jin et al, 2016;Shimomura et al, 2016). However, MSCs derived from PB did not achieve the same confluence until about 21 days after primary culture (Chen et al, 2019). It takes longer to obtain the culture-expanded PB-MSCs than other tissue-derived MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MSCs derived from bone marrow, synovium or adipose tissue reached 80-90% confluence within 7 to 14 days (Zhang et al, 2014;Jin et al, 2016;Shimomura et al, 2016). However, MSCs derived from PB did not achieve the same confluence until about 21 days after primary culture (Chen et al, 2019). It takes longer to obtain the culture-expanded PB-MSCs than other tissue-derived MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other tissue-derived MSCs, the culture of PB-MSCs was relatively difficult, which resulted in less reports of its application in vivo, but it does not affect its application prospects. On the contrary, it is ethically more suitable for clinical application due to its unique advantages, such as minimally invasive sample acquisition procedure, repeatable sampling, and high recognition of patients (Fu et al, 2014a;Fu et al, 2014b;Wang et al, 2016a;Chen et al, 2019). In this review, we have summarized all the currently published researches on the use of PBSCs for cartilage repair and regeneration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple bioprinting applications in vascular models, soft-tissue models, and bone models manufactured with extrusion-based printing technology have been well-developed in recent years (Ahlfeld et al, 2017;Paxton et al, 2017;Ahlfeld et al, 2018). One major advantage of its bioprinting application is that the hydrogels of extrusion-based printing is capable to fabricate products with high cell density (> 1 × 10 6 cells ml −1 ) (Petta et al, 2018;Taylor et al, 2018;Chen et al, 2019).…”
Section: Extrusion-based Printingmentioning
confidence: 99%
“…Chitosan is a kind of mucopolysaccharide widely existed in nature, which is important component of connective tissue with complexation, bacteriostasis, adsorption, and antioxidant effects (Molinaro et al, 2002;Jayakumar et al, 2005). Recent reports demonstrated that chitosan can be gelated in an acidic pH or a non-solvent condition (Ribeiro et al, 2017;Xu et al, 2017;Chen Y. R. et al, 2019), and further be prepared for chitosanbased hydrogel scaffolds. Chitosan has good biocompatibility and biodegradability; therefore, it is a kind of tissue-engineering material with wide application prospects and can be considered as a potential material for cartilage repair in regenerative medicine fields.…”
Section: Chitosanmentioning
confidence: 99%